Removal of Phenol and 4-Chlorophenol from Aqueous Solutions by Olive Stone-Based Activated Carbon - Mourad Termoul; Benaouda Bestani; Nouredine Benderdouche; Mostefa Belhakem; Emmanuel Naffrechoux (Adsorption Science & Technology)
The evaluation of agricultural by-products as a means of removing pollutants from contaminated wastewater is attracting increasing interest for sustainable development applications. The present work deals with the removal of phenol and 4-chlorophenol from aqueous solutions by chemically activated olive stones. The olive stones were soaked in 50% phosphoric acid for 3 h at 443 K. After washing, the product was activated in an inert atmosphere for 2 h or 3 h at temperatures within the range 873–1023 K. The carbons thus prepared were characterized by Methylene Blue and iodine adsorption, N 2 adsorption at 77 K in conjunction with the BET equation, scanning electron microscopy (SEM) and Boehm titrations. The sorption capacity towards both pollutants was determined by fitting the Langmuir model to the adsorption isotherms. The optimum activation temperature and time were 1023 K and 3 h, respectively. A maximum adsorption capacity of 189 mg/g was obtained for phenol and 436 mg/g for 4-chlorophenol. In comparison, the Merck and Aldrich commercial-grade powdered activated carbons ranked lower with adsorption capacities of 145 mg/g and 179 mg/g for phenol and 244 mg/g and 316 mg/g for 4-chorophenol, respectively.